2008
DOI: 10.1007/s11135-008-9216-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and total factor productivity of crop production at NUTS1 level in Turkey: Malmquist index approach

Abstract: Agriculture, TFP Change, DEA, Turkey,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…In the selection of evaluation indicators, some early scholars took traditional production factors such as land, intermediate factors and labor as input factors (Lin, 1992;Wen, 1993), and most scholars took production factors such as land, water resources, labor, pesticides and chemical fertilizers as input factors (Benedetti et al, 2019;Zhang et al, 2021). In the selection of output factor indicators, scholars generally choose the total grain output as the output index (Yao and Xuan, 2019), while some use the total agricultural output value per unit of cultivated land (Armagan et al, 2010;Kumbhakar et al, 2014) or agricultural added value (Gebregziabher et al, 2012).…”
Section: Calculation Of Grain Production Efficiencymentioning
confidence: 99%
“…In the selection of evaluation indicators, some early scholars took traditional production factors such as land, intermediate factors and labor as input factors (Lin, 1992;Wen, 1993), and most scholars took production factors such as land, water resources, labor, pesticides and chemical fertilizers as input factors (Benedetti et al, 2019;Zhang et al, 2021). In the selection of output factor indicators, scholars generally choose the total grain output as the output index (Yao and Xuan, 2019), while some use the total agricultural output value per unit of cultivated land (Armagan et al, 2010;Kumbhakar et al, 2014) or agricultural added value (Gebregziabher et al, 2012).…”
Section: Calculation Of Grain Production Efficiencymentioning
confidence: 99%
“…Yapılan hesaplamalar sonucunda bölgelere ait skor ortalamaları her ne kadar birbirine yakın olarak gözükse de bir sıralama yapıldığında ilk dört sırayı Ege, Batı Marmara, Akdeniz ve Doğu Marmara Bölgelerinin izlediği, son dört sırayı ise, Batı Karadeniz, Orta Doğu Anadolu, Güney Doğu Anadolu ve Kuzey Doğu Anadolu bölgelerinin aldığı görülmektedir (Çizelge 5). Bu hesaplamalarda yer alan çalışmalar aynı girdi ve çıktılara göre yapılmamış olsa da sıralama açısından incelendiğinde, sonuçların Armağan et al, (2010) ve Özden ve Armağan (2012) tarafından yapılan çalışmalarla uyumlu olduğu görülmektedir. Bitkisel üretimde teknik etkinlik hesaplamalarının yapıldığı çalışmalardan elde edilen etkinlik ortalamalarının, bölgelere göre tarımsal etkinlik ya da bitkisel üretim etkinliklerinin hesaplandığı çalışmalarla uyumlu olması, bu tarz çalışmaların sonuçlarının geneli yansıtması ve kullanılabilirliği açısından önemlidir.…”
Section: Genel Değerlendi̇rme Ve çIkarimlarunclassified
“…Guyomard [17] measured the agricultural production efficiency of French farms by the DEA method; the results showed that technological progress played a key role in improving agricultural production efficiency. Armagan [18] analyzed the TFP of agricultural production in Turkey by using the DEA-Malmquist productivity index and found that the backward technical level was one of the main factors that affected the decline of the growth rate of agricultural TFP. Wouterse [19] found that a significant relationship existed between labor transfer and the technical efficiency of grain production.…”
Section: Introductionmentioning
confidence: 99%